The Implications of Parliament's Exercise of Section 91(24) Powers for the Inherent Right of Self-Government - McNeil, Kent (Osgoode Digital Commons, 2002)
This is a research report that was prepared for the Assembly of First Nations, Office of the B.C. Regional Vice-Chief.